(untitled) (Research, Society and Development, 2022)
Rural education is configured in an educational modality and specific public policy that serves the peasant populations inhabiting the most diverse territories in Brazil. However, one of the main challenges that interfere in this modality is the issue of the educational curriculum implemented in basic education institutions. Thus, the objective of this research is to understand and analyze the main approaches on perspectives, notes and reflections about the school curriculum in the context of rural education in Brazilian schools. Therefore, to design this study, qualitative approaches were used, and the bibliographic and documentary study was adopted as a methodological procedure. The results indicate that rural education has conquered numerous demands and guidelines in the legislative sphere. However, scholars in the area demonstrate that in most rural schools an educational curriculum is implemented in an urban-centric perspective that does not consider the reality and specificities of the people who inhabit the territories of water, forests, forests, roads and branches. In addition, the implementation of this curriculum generates several problems for students. Given this, it is necessary to develop curricula that consider the reality of these subjects, and development of continuing education for teachers so that they can make curricular adaptations.